Reflections on using a community-led research methodology to explore experiences of living with food insecurity. (25th October 2017) - Greenaway, Lesley; McDowell, Jacqui
Abstract: This article explores how community-led research in practice relates to the theory and aspirations of a community-led research methodology and how this approach can provide a unique opportunity to increase our understanding about the lived experiences of food insecurity. As an approach, community-led research has growing influence and relevance for communities, organizations, research commissioners, funders and policy makers. This article provides insights and learning for these stakeholders that we discovered in our experience of the 'Living with food insecurity' community-led research project. We draw on a range of sources including: community-led research literature, materials developed to support the project, feedback from the research teams, and reflective conversations between the research commissioner and the research specialist who was engaged to support the process. We start by setting out the context for food insecurity in Scotland and identify the research gap that led to the research project. We then discuss some pertinent research challenges in the context of this project, and explore how each of three distinct communities developed different models of community-led research. Learning from this project suggests that community-led research design needs to embrace divergence and facilitate research partnerships that are flexible, open and find ways to 'live' out the principles of community-led research in ways that are meaningful to a particular community and its stakeholders.